Sistema informático para la gestión administrativa de la empresa radial “suprema 93.1 FM” de la ciudad de ventanas - Lucas Castro, Roger Zacarías (2018)
This project describes the development and use of the computer system for the administrative management of the radial company -suprema 93.1 FM‖ of the city of windows. System that allows to take into account certain administrative processes of this radial company. Taking into account the problematic since, to this, the development of the computer system is due, the disadvantages that arise within the radial company are: Duplicity of documents, loss of documents and loss of time in the processes such as advertising contracts and radial programming. The proposal to solve the problem is for the SUPREMA 93.1 FM radio company in the city of Ventanas, to have availability, agility and accurate information, when required by the users, in addition; to promote the realization of more useful computer systems for the same company, therefore, this project is divided into 3 chapters. In the first chapter is, the diagnosis of needs and requirements is detailed the domain list in which it will be established and execute the copy or prototype, information, requirements, reasons for execution of the proposal, detailing the benefits of the prototype and the same way to meet the needs. The second chapter is, the development of the prototype, in this part of the chapter specifies the requirements and their important functions to satisfy the users, the hypothesis that protects the prototype, its objectives, and the procedures or solutions, more obvious to the application of logical and physical way to prepare the prototype.